Between politics and economics - Hans-Eberhard Zaunitzer (Intereconomics, 1967)
The Federal Republic of Germany considers trade between itself and East Germany not as foreign, but as domestic trade. Since the division of Germany these economic contacts have often given rise to heated discussion and bitter criticism. The close connection between political and economic aims is constantly engendering new fuel. The collision of two completely opposed systems raises a multiplicity of fresh problems.
Keywords: 330; German Domestic Trade